Separation process principles : chemical and biochemical operations - Henley, Ernest J.; Seader, J. D.; Roper, D. Keith (Hoboken, NJ : Wiley, 2011)
"Completely rewritten to enhance clarity, this third edition provides engineers with a strong understanding of the field. With the help of an additional co-author, the book presents new information on bioseparations throughout the chapters. A new chapter on mechanical separations covers settling, filtration, and centrifugation, including mechanical separations in biotechnology and cell lysis. Boxes help highlight fundamental equations. Numerous new examples and exercises are integrated throughout as well. In addition, frequent references are made to the software products and simulators that will help engineers find the solutions they need"--
Machine generated contents note: About the Authors. -- Preface to the Third Edition. -- Nomenclature. -- Dimensions and Units. -- PART 1 FUNDAMENTAL CONCEPTS. -- 1. Separation Processes. -- 1.0 Instructional Objectives. -- 1.1 Industrial Chemical Processes. -- 1.2 Basic Separation Techniques. -- 1.3 Separations by Phase Addition or Creation. -- 1.4 Separations by Barriers. -- 1.5 Separations by Solid Agents. -- 1.6 Separations by External Field or Gradient. -- 1.7 Component Recoveries and Product Purities. -- 1.8 Separation Factor. -- 1.9 Introduction to Bioseparations. -- 1.10 Selection of Feasible Separations. -- Summary References Study Questions Exercises. -- 2. Thermodynamics of Separation Operations. -- 2.0 Instructional Objectives. -- 2.1 Energy, Entropy, and Availability Balances. -- 2.2 Phase Equilibria. -- 2.3 Ideal-Gas, Ideal-Liquid-Solution Model. -- 2.4 Graphical Correlations of Thermodynamic Properties. -- 2.5 Nonideal Thermodynamic Property Models. -- 2.6 Liquid Activity-Coefficient Models. -- 2.7 Difficult Mixtures. -- 2.8 Selecting an Appropriate Model. -- 2.9 Thermodynamic Activity of Biological Species. -- Summary References Study Questions Exercises. -- 3. Mass Transfer and Diffusion. -- 3.0 Instructional Objectives. -- 3.1 Steady-State, Ordinary Molecular Diffusion. -- 3.2 Diffusion Coefficients (Diffusivities). -- 3.3 Steady- and Unsteady-State Mass Transfer Through Stationary Media. -- 3.4 Mass Transfer in Laminar Flow. -- 3.5 Mass Transfer in Turbulent Flow. -- 3.6 Models for Mass Transfer in Fluids with a Fluid-Fluid Interface. -- 3.7 Two-Film Theory and Overall Mass-Transfer Coefficients. -- 3.8 Molecular Mass Transfer in Terms of Other Driving Forces. -- Summary References Study Questions Exercises. -- 4. Single Equilibrium Stages and Flash Calculations. -- 4.0 Instructional Objectives. -- 4.1 Gibbs Phase Rule and Degrees of Freedom. -- 4.2 Binary Vapor-Liquid Systems. -- 4.3 Binary Azeotropic Systems. -- 4.4 Multicomponent Flash, Bubble-Point, and Dew-Point Calculations. -- 4.5 Ternary Liquid-Liquid Systems. -- 4.6 Multicomponent Liquid-Liquid Systems. -- 4.7 Solid-Liquid Systems. -- 4.8 Gas-Liquid Systems. -- 4.9 Gas-Solid Systems. -- 4.10 Multiphase Systems. -- Summary References Study Questions Exercises. -- 5. Cascades and Hybrid Systems. -- 5.0 Instructional Objectives. -- 5.1 Cascade Configurations. -- 5.2 Solid-Liquid Cascades. -- 5.3 Single-Section Extraction Cascades. -- 5.4 Multicomponent Vapor-Liquid Cascades. -- 5.5 Membrane Cascades. -- 5.6 Hybrid Systems. -- 5.7 Degrees of Freedom and Specifications for Cascades. -- Summary References Study Questions Exercises. -- PART 2 SEPARATIONS BY PHASE ADDITION OR CREATION. -- 6. Absorption and Stripping of Dilute Mixtures. -- 6.0 Instructional Objectives. -- 6.1 Equipment for Vapor-Liquid Separations. -- 6.2 General Design Considerations. -- 6.3 Graphical Method for Trayed Towers. -- 6.4 Algebraic Method for Determining N. -- 6.5 Stage Efficiency and Column Height for Trayed Columns. -- 6.6 Flooding, Column Diameter, Pressure Drop, and Mass Transfer for Trayed Columns. -- 6.7 Rate-Based Method for Packed Columns. -- 6.8 Packed-Column Liquid Holdup, Diameter, Flooding, Pressure Drop, and Mass-Transfer -- Efficiency. -- 6.9 Concentrated Solutions in Packed Columns. -- Summary References Study Questions Exercises. -- 7. Distillation of Binary Mixtures. -- 7.0 Instructional Objectives. -- 7.1 Equipment and Design Considerations. -- 7.2 McCabe-Thiele Graphical Method for Trayed Towers. -- 7.3 Extensions of the McCabe-Thiele Method. -- 7.4 Estimation of Stage Efficiency for Distillation. -- 7.5 Column and Reflux-Drum Diameters. -- 7.6 Rate-Based Method for Packed Distillation Columns. -- 7.7 Introduction to the Ponchon-Savarit Graphical Equilibrium-Stage Method for Trayed -- Towers. -- Summary References Study Questions Exercises. -- 8. Liquid-Liquid Extraction with Ternary Systems. -- 8.0 Instructional Objectives. -- 8.1 Equipment for Solvent Extraction. -- 8.2 General Design Considerations. -- 8.3 Hunter-Nash Graphical Equilibrium-Stage Method. -- 8.4 Maloney-Schubert Graphical Equilibrium-Stage Method. -- 8.5 Theory and Scale-up of Extractor Performance. -- 8.6 Extraction of Bioproducts. -- Summary References Study Questions Exercises. -- 9. Approximate Methods for Multicomponent, Multistage Separations. -- 9.0 Instructional Objectives. -- 9.1 Fenske-Underwood-Gilliland (FUG) Method. -- 9.2 Kremser Group Method. -- Summary References Study Questions Exercises. -- 10. Equilibrium-Based Methods for Multicomponent Absorption, Stripping, -- Distillation, and Extraction. -- 10.0 Instructional Objectives. -- 10.1 Theoretical Model for an Equilibrium Stage. -- 10.2 Strategy of Mathematical Solution. -- 10.3 Equation-Tearing Procedures. -- 10.4 Newton-Raphson (NR) Method. -- 10.5 Inside-Out Method. -- Summary References Study Questions Exercises. -- 11. Enhanced Distillation and Supercritical Extraction. -- 11.0 Instructional Objectives. -- 11.1 Use of Triangular Graphs. -- 11.2 Extractive Distillation. -- 11.3 Salt Distillation. -- 11.4 Pressure-Swing Distillation. -- 11.5 Homogeneous Azeotropic Distillation. -- 11.6 Heterogeneous Azeotropic Distillation. -- 11.7 Reactive Distillation. -- 11.8 Supercritical-Fluid Extraction. -- Summary References Study Questions Exercises. -- 12. Rate-Based Models for Vapor-Liquid Separation Operations. -- 12.0 Instructional Objectives. -- 12.1 Rate-Based Model. -- 12.2 Thermodynamic Properties and Transport-Rate Expressions. -- 12.3 Methods for Estimating Transport Coefficients and Interfacial Area. -- 12.4 Vapor and Liquid Flow Patterns. -- 12.5 Method of Calculation. -- Summary References Study Questions Exercises. -- 13. Batch Distillation. -- 13.0 Instructional Objectives. -- 13.1 Differential Distillation. -- 13.2 Binary Batch Rectification. -- 13.3 Batch Stripping and Complex Batch Distillation. -- 13.4 Effect of Liquid Holdup. -- 13.5 Shortcut Method for Batch Rectification. -- 13.6 Stage-by-Stage Methods for Batch Rectification. -- 13.7 Intermediate-cut Strategy. -- 13.8 Optimal Control by Variation of Reflux Ratio. -- Summary References Study Questions Exercises. -- PART 3 SEPARATIONS BY BARRIERS AND SOLID AGENTS. -- 14. Membrane Separations. -- 14.0 Instructional Objectives. -- 14.1 Membrane Materials. -- 14.2 Membrane Modules. -- 14.3 Transport in Membranes. -- 14.4 Dialysis. -- 14.5 Electrodialysis. -- 14.6 Reverse Osmosis. -- 14.7 Gas Permeation. -- 14.8 Pervaporation. -- 14.9 Membranes in Bioprocessing. -- Summary References Study Questions Exercises. -- 15. Adsorption, Ion Exchange, Chromatography, and Electrophoresis. -- 15.0 Instructional Objectives. -- 15.1 Sorbents. -- 15.2 Equilibrium Considerations. -- 15.3 Kinetic and Transport Considerations. -- 15.4 Equipment for Sorption Systems. -- 15.5 Slurry and Fixed-Bed Adsorption Systems. -- 15.6 Continuous, Countercurrent Adsorption Systems. -- 15.7 Ion-Exchange Cycle. -- 15.8 Electrophoresis. -- Summary References Study Questions Exercises. -- PART 4 SEPARATIONS THAT INVOLVE A SOLID PHASE. -- 16. Leaching and Washing. -- 16.0 Instructional Objectives. -- 16.1 Equipment for Leaching. -- 16.2 Equilibrium-Stage Model for Leaching and Washing. -- 16.3 Rate-Based Model for Leaching. -- Summary References Study Questions Exercises. -- 17. Crystallization, Desublimation, and Evaporation. -- 17.0 Instructional Objectives. -- 17.1 Crystal Geometry. -- 17.2 Thermodynamic Considerations. -- 17.3 Kinetics and Mass Transfer. -- 17.4 Equipment for Solution Crystallization. -- 17.5 The MSMPR Crystallization Model. -- 17.6 Precipitation. -- 17.7 Melt Crystallization. -- 17.8 Zone Melting. -- 17.9 Desublimation. -- 17.10 Evaporation. -- 17.11 Bioproduct Crystallization. -- Summary References Study Questions Exercises -- 18. Drying of Solids. -- 18.0 Instructional Objectives. -- 18.1 Drying Equipment. -- 18.2 Psychrometry. -- 18.3 Equilibrium-Moisture Content of Solids. -- 18.4 Drying Periods. -- 18.5 Dryer Models. -- 18.6 Drying of Bioproducts. -- Summary References Study Questions Exercises. -- PART 5 MECHANICAL SEPARATION OF PHASES. -- 19. Mechanical Phase Separations. -- 19.0 Instructional Objectives. -- 19.1 Separation-Device Selection. -- 19.2 Industrial Particle-Separator Devices. -- 19.3 Design of Particle Separators. -- 19.4 Design of Solid-Liquid Cake-Filtration Devices Based on Pressure Gradients. -- 19.5 Centrifuge Devices for Solid-Liquid Separations. -- 19.6 Wash Cycles. -- 19.7 Mechanical Separations in Biotechnology. -- Summary References Study Questions Exercises. -- Answers to Selected Exercises. -- Index.
Includes bibliographical references and index.
Keywords: Separation (Technology) -- Textbooks